Plasma confinement by means of poloidal-toroidal magnetic surfaces - Maksyuta, M.V.; Golovach, G.P.; Martysh, Ye.V. (Вопросы атомной науки и техники, 2011)
The paper proposes to perform plasma magnetic confinement in the constructions where plasma streams flow by knotted trajectories. It is shown that in this case due to more complicated topology of plasma circulation, a quasi-stationary equilibrium may be carried out without an external magnetic field, and i.e. plasma is self-confined by the self-generation of poloidal-toroidal magnetic surfaces. This phenomenon may serve as a mechanism of a ball-lightning origination and existence.